OBSERVATIONS ON THE FISHERY AND BIOLOGY OF MEGALASPIS CORDYLA (LINNAEUS) AT VIZHINJAM - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
The fishery for Megalaspis cordyla (locally called Vangoda) formed on anaverage 6.63% of the total marine fish landings at Vizhinjam. An increasing trendin the fishery was noticed from 1969 to 1973. Hooks and lines and drift netscontributed to about 95.8% of the catch. Post-monsoon period was the best seasonfor the landings of M. cordyla.